Discovery of direct inhibitor of KRAS oncogenic protein by natural products: a combination of pharmacophore search, molecular docking, and molecular dynamic studies - Samaneh Hashemi; Amirhossein Sharifi; Sara Zareei; Ghazale Mohamedi; Mahmood Biglar; Massoud Amanlou (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Aberrant signaling by oncogenic RAS proteins occurs in almost all human tumors. One of the promising strategies to overcome such cancers is the inhibition of KRAS protein, a subtype of RAS family involved in cell growth, differentiation, and apoptosis, through preventing its effector, SOS1, from being attached to the protein. Experimntal approach: Herein, a virtual screening process was performed using pharmacophore search, molecular docking, and molecular dynamic simulations. A pharmacophore model was created to indicate essential features for a KRAS inhibitor and used for screening the National Cancer Institution (NCI) database to retrieve similar compounds to the pharmacophore model with more than 70% similarity. Chosen compounds were then docked into KRAS and four compounds were selected based on the highest binding scores. Next, a similarity search was done in the whole PubChem database to increase the number of potential inhibitors. The filtered compounds were docked again into KRAS and three of them were selected for molecular dynamic simulation. Findings / Results: Compounds 1a, 2d, and 3a can inhibit SOS-iKRASG12D interaction due to the higher number of interactions with the protein. Moreover, they achieved the equilibrium faster than the approved inhibitor. Conclusion and implications: Auriculasin, a polyphenol flavonoid, can be considered as a potential inhibitor of SOS1-KRAS interaction. This compound seems to be a stronger anticancer than 9LI, a known inhibitor of KRAS, due to its better docking scores. Moreover, this compound can be an appropriate candidate to be formulated as an oral drug.